The Effect of Warm Intravenous Fluid on Postoperative Pain: A Double-Blind Clinical Trial - Mansoreh Shafaeiyan; Fatemeh Ghods; Fatemeh Rahbar; Zahra Daneshi; Leiyla Sadati; Banafsheh Mashak; Jafar Moradi; Hojjat Torkmandi (Zanjan University of Medical Sciences and Health Services, 2020)
Background: Hypothermia is likely to cause enormous dangers for patients undergoing cesarean section. Objectives: This study aims to comparison between the effect of using two different temperatures of IV fluids (37.5°C versus 21-22°C) in body temperature drop and the post-operative pain. Methods: This experimental study was double-blind clinical trial, conducted in 2017 (April, 2017 to January, 2018). The method of sampling was simple random sampling. The randomly selected mothers, undergoing cesarean section, were assigned into two groups of equal number (the hexagonal blocks of A and B) in this clinical trial. The experimental and control group participants received IV fluid at the operation room temperature (25°C) and the IV fluid of 37.5°C, respectively. The core intraoperative body temperature was measured by Microlife Infrared Tympanic-IR100 thermometer. Severity of the experimental and control group patients' post-operative pain was also measured and compared for 24 hours (since when the patients were discharged from the recovery ward) by the VAS (0-10). Results: A total of 80 patients underwent this study. The demographic information of the two group members showed no difference of significance (p>0.05). The average intraoperative body temperature of the experimental group participants was higher in the level (p=0.001) of significance than that of the control group members. There was no difference of significance (p=0.41) between the mean severity of pain of both groups' participants in the first 24 hours. Conclusion: The intraoperative IV fluid warming seems not to have any tranquilizing effect in the postsurgery pain.